PULSATILE DRUG DELIVERY: A STRATEGY FOR TREATING CHRONOTHERAPEUTIC AILMENTS - J., GOMATHI; B., VEERALAKSHMI; M. F., FARZANA AFFRIN (International Journal of Current Pharmaceutical Research, 2023)
Modern drug delivery systems have been promoted to a unique notion of chronopharmacology, i.e., the ability to provide the medicament to a patient in a staggered profile, as the discipline of chronobiology has advanced. The main disadvantage of developing such a delivery system that fits the circadian cycle is the lack of accurate technology (Pulsatile drug delivery system, PDDS). Pulsatile devices are gaining popularity because they deliver the medicine to the correct region of action at the correct time, allowing for spatial and temporal dosing and compliance among patients. These technologies are meant to work with the body's natural circadian cycle. The circadian rhythm affects various biological systems in humans, including metabolism, physiology, behaviour, sleep patterns, hormone synthesis, and so on. This article addresses several methods, such as osmotic systems, capsular systems, single and multiple-unit programable devices that rely on soluble or erodible polymer coatings, and the usage of rupturable membranes. The present review covered the rationale for the creation of pulsatile drug delivery systems, benefits, limitations the types of diseases that require pulsatile release, categorization, and assessments of pulsatile system of drug delivery.